Tata Kelola Sponsorship Industri Kesehatan Global: Sebuah Scoping Review Untuk Pembelajaran Kebijakan di Indonesia - Pramudita, Gustian Yondi; Junadi, Purnawan (Jurnal Ners, 2025)
Collaboration between the health industry and healthcare professionals (HCPs) is essential for innovation but risks creating conflicts of interest (COI) and gratification. In Indonesia, the existing hybrid governance framework has proven ineffective due to a lack of transparency and coordinated enforcement, exacerbated by the normalization of gratification practices. The enactment of Health Law No. 17 of 2023, which could fragment ethical oversight, adds urgency for reform. This study aims to map global sponsorship governance policies to provide lessons for Indonesia. Conducted as a scoping review following PRISMA-SCR guidelines, this study analyzed 32 relevant documents from 2015-2025, selected from an initial 2,067 articles. The results identify three main models: a transparent legislative mandate (US), industry self-regulation with a "consent loophole" (Europe), and a hybrid model with implementation gaps (Indonesia). The key "Transparency Paradox" finding indicates that public disclosure alone is insufficient without consistent enforcement. This review highlights a global trend towards legally mandated transparency, with precedents from Spain and Brazil. As a recommendation, Indonesia’s legal framework must be activated by adopting a "Sunshine Act"-like legislative mandate and establishing a coordinated, cross-sectoral oversight task force.